Stimulasi kecerdasan bayi dengan pijat bayi di desa Muara Purba Nauli - Eliya Lia Wardayani (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2022)
ABSTRACT Today the parents were often preoccupied with finding a tutor or a private teacher to teach their children at home to be a smart student. Which was not necessary if a mother begins to stimulate her child's intelligence from infancy. We know that the golden period in which a child's brain development was at age 1-2 what was commonly called "gold period" in the child. Padangsidimpuan was a city that was developing and catching up of other regions. The Reasonable for parents in this city preoccupied to finding quality schools and qualified teachers for their children. A child's success depends not on where were their school, but on the quality of their life. A child of good intelligence will be a child that can boast parents, religion, nation and state. Because a child's intelligence will also influence their psychological life and emotional maturity later in life. Baby massage was one of the three basic needs of touch because in practice the baby's massage contains the touching elements of affection, voice or speech, eye contact, movement and massage. Baby massage was one type of stimulation that stimulates both the structure and the function of the cells in the brain. Counseling cadre posyandu for the introduction and knowledge of infant massage. Did a demonstration of a baby massage that started from watching a baby video, doing a baby massage on a baby panthom. This activity is expected to change the mother's perspective that massage is only done by a massage therapist but the best massage/touch is the touch/massage done by the people closest to the baby. Keywords: stimulation, intelligence, baby massage